KETERBUKAAN INFORMASI PUBLIK DALAM PERSPEKTIF GOVERNABILITY - Sofian Munawar Asgart (Jurnal Ilmu Politik dan Pemerintahan, 2011)
Information is like oxygen for democracy. Freedom of information can be a spirit of democratization that offers freedom while at the same responsibilities. Freedom of information, on the one hand to encourage public access to information widely. While on the other hand, freedom of information and also to give birth governability in which the state can enable him to effectively and efficiently without compromising the principles of democracy. As an independent commission tasked with ensuring security of access to public information, the Information Commission can provide a strategic contribution. Attendance Information Commission not only had to answer a public need for access to information, but can also help governments provide supply information that is authentic and valid, so the government can take the right decisions based on accurate and objective information. Various studies of political development in countries that have enjoyed political stability and social harmony shows that freedom of information and people's right to information play a central role in the overall process of democratic politics. There is no a country is able to guarantee political stability and social order in sustainability, unless the system is facilitated by guarantees of freedom of information. In this context, freedom of public information to find its relevance to the governability.